The aqmeological framework for modern higher education as a step towards sustainable development of society - Kryvylova, Olena; Sosnickaya, Natalya; Oleksenko, Karina; Oleksenko, Roman; Khavina, Irina (Linguistics and Culture Review, 2021)
The article considers the issues, connected with the development of acmeological basis of modern higher education, which contributes to the fulfillment of requirements for the provision of sustainable development of society in the context of formation of human ability to learn to live in order to contribute to the own personality prosperity and be able to act, demonstrating independence, judgement independence and personal responsibility. The research results on the use of the acmeological approach in the professional training of applicants for higher education, the organization of acmeological impact and support of future specialists during the professional formation period are presented. Theoretically justified the implementation of the mentioned psychological and pedagogical condition at the professional training system level, sets the necessary strategy in achieving integrative competence by higher education applicants (the organization of educational process depends on this level); at the level of the educational process, sets the action algorithm for achieving the results of mastering theoretical knowledge, practice-oriented and independent activity of a specific topic and discipline as a whole (allows you to use the full potential of the chosen topic to achieve optimum performance in mastering general and special competencies).